Implikasi Perizinan Sektor Berbasis Lahan Terhadap Kondisi Kawasan Hutan Di Provinsi Riau - Suprapto Suprapto; San Afri Awang; Ahmad Maryudi; Wahyu Wardhana (Universitas Lambung Mangkurat, 2019)
Forest resources can be utilized through various activities in the land-based sector, including forestry, plantations, and mining. The implications of the issuance of various permits are indicated to cause changes in the area of forest and land cover. This paper aims to analyze and explain the implications of the various land-based sector licenses that have been issued by the local government and the central government on the condition of forest areas in Riau Province. The research method was carried out with qualitative descriptive analysis, through interviews, spatial analysis, and review and tracking documents. The results of the study showed that during the period 1986-2017 there had been a change in the area of forest area and land cover. The biggest changes in forest areas occur due to the conversion of forest areas into plantations, while the largest land cover changes in successive classes are land cover for plantations (Pk), forest plantations (Ht) and mining (Pn). Some of the recommendations that we propose are the temporary dismissal of licenses in the Riau forest area, the rearrangement of all licenses related to forest areas, increasing integrity and willingness of all parties in Riau and the central government in sustainable forest management.